Activity of a Phenolic Dibenzylsulfide against New World Arenavirus Infections. Issue 4 (August 2014) - Gowen, Brian B; Jung, Kie-Hoon; Sefing, Eric J; Wong, Min-Hui; Westover, Jonna B; Smee, Donald F
Background: Junín virus (JUNV) and several other clade B New World arenaviruses cause human disease ranging from mild febrile illness to severe viral haemorrhagic fever. These viruses pose a significant threat to national security and safe and effective therapies are limited except in Argentina, where immune plasma is the standard of care for treating JUNV infection in cases of Argentine haemorrhagic fever. Methods: An in vitro screen of the Chemtura library identified several compounds with activity against Tacaribe virus (TCRV), a clade B arenavirus closely related to JUNV. Of these compounds, D746, a phenolic dibenzylsulfide, was further pursued for additional in vitro studies and evaluated in the AG129 mouse TCRV infection model. Results: D746 was found to act during an early to intermediate stage of the TCRV replication cycle and μM range activity was confirmed by virus yield reduction assays with both TCRV and JUNV. Although intraperitoneal twice daily treatment regimens were found to be highly effective when started 2 h prior to TCRV challenge in AG129 mice, post-exposure treatment initiated 3 days after infection was not efficacious. Interestingly, despite the pre-exposure treatment success, D746 did not reduce serum or tissue virus titres during the acute infection. Moreover, D746 elicited ascites fluid accumulation in mice during, as well as independent of, infection. Conclusions: Our findings suggest that D746 may be altering the host response to TCRV infection in AG129 mice in a way that limits pathogenesis and thereby protects mice from otherwise lethal infection in the absence of measurable reductions in viral burden.